Стратегія розвитку підприємства - Поварнін, Богдан Володимирович; Povarnin, Bohdan (ЦНТУ, 2024)
Кваліфікаційна робота за ступенем вищої освіти "Магістр" на тему: "Стратегія розвитку підприємства" Актуальність теми полягає в тому що Фірма яка давно була одним лідерів на ринку світлопрозорих конструкцій, з появою нових потужних конкурентів почала втрачати свої позиції. Одним з ефективних виходів з даної ситуації полягає в розробці нової стратегії підприємства, яка дозволить повернути втрачені позиції на території України в усіх її регіонах разом з запуском нових потужностей і агресивною маркетинговою стратегією. Стратегія дозволить активізувати діяльність Фірми в регіонах, завдяки створенню дилерських представництв, які за допомогою активного використання комплексу маркетингу збільшать присутність на ринку товарів Фірми і відповідно її ринкову частку. Qualification work for the degree of higher education "Master" on the topic: "Enterprise Development Strategy" The relevance of the topic lies in the fact that the Company, which has long been one of the leaders in the market of translucent structures, began to lose its positions with the emergence of new powerful competitors. One of the effective ways out of this situation is to develop a new strategy for the company, which will allow it to regain lost positions in Ukraine in all its regions, along with the launch of new facilities and an aggressive marketing strategy. The strategy will allow the Company to intensify its activities in the regions, thanks to the creation of dealer offices, which, through the active use of the marketing complex, will increase the presence of the Company's products on the market and, accordingly, its market share.
Enterprise development strategy
Keywords: стратегія розвитку підприємства; enterprise development strategy